Medieval and renaissance logic in Spain : acts of the 12 th European Symposium on Medieval Logic and Semantics, held at the University of Navarre (Pamplona: 26-30 Mayo 1997). Hildesheim: Georg Olms Verlag, 2000 - López Rosende, Diego (2001)
Fil: López Rosende, Diego. Universidad de Buenos Aires; Argentina.